Metal complexed-enzymatic hydrolyzed chitosan improves moisture retention of fiber papers by migrating immobilized water to bound state. (1st May 2020) - Wang, Huijuan; Cui, Heping; Wang, Xuejiao; Lin, Chao; Xia, Shuqin; Hayat, Khizar; Hussain, Shahzad; Tahir, Muhammad Usman; Zhang, Xiaoming
Graphical abstract: Highlights: Metal complexed-enzymatic hydrolyzing prepared chitosan of narrower M W distribution. Chitosan with M W of 5.67 kDa could hold moisture and retain a lower a W . Mounting newly formed chain-end hydrophilic groups increased moisture retention. Abstract: To obtain chitosan (CTS) with narrower molecular weight distribution, CTS with weight-average molecular weight ( M W ) of 197.30 kDa was first metal complexed and then degraded into five CTSs with M W of 107.90, 56.48, 10.40, 5.67 (CTS-4) and 3.66 kDa. Decrease of M W did not cause a significant change in chemical structure of the residue CTS, but the crystal structure was transformed significantly. The moisture retention increased firstly and then decreased as the M W of CTS decreased. CTS-4 was superior to CTSs with other M W and propylene glycol in terms of the moisture retention. The lower water activity and increase of net isosteric heat were observed in CTS-4, which was due to the migration of immobilized water to a bound-state caused by mounting newly formed chain-end hydrophilic groups per unit weight. CTS-4 could effectively improve moisture retention, showing a potential to substitute commonly used humectant such as propylene glycol.